An empirical examination of sustainability for multinational firms in China: Implications for cleaner production. (1st January 2020) - D'Souza, Clare; McCormack, Silvia; Taghian, Mehdi; Chu, Mei-Tai; Sullivan Mort, Gillian; Ahmed, Tanvir
Abstract: Globally, sustainability is emerging as a dynamic area of inquiry and innovation. This research is an exploratory study that sought to examine multinational corporations in China. The research aims to examine the pressure from parent companies and develop a conceptual framework to improve sustainability from a set of indicators; it further recognizes the underlying motivators for implementing sustainability practices and discusses their implications. Lastly, it reports the differences in sustainability performance based on firm size which provides insights for addressing sustainability initiatives. Recommendations are offered in the final section based on enough latitude and flexibility within host countries to improve sustainability practices. Due to the exploratory nature of this study, the data were analyzed based on regressions, factor analysis, cluster analysis and one-way ANOVA on a sample of 229 executive responses analyzed from multinationals in China. Many variables were explored, such as environmental practices; social practices; internal pressures to improve environmental performance; external pressures to improve environmental performance; internal pressures to improve external environmental performance; and barriers to adoption. The article concludes by arguing that greater emphasis on management in the host country is required for sustainability practices and makes an important theoretical and practical contribution to the literature within this realm. Graphical abstract: A framework in relation to the sustainability actions of MNCs was developed in this study to help understand MNC sustainability disposition and host country discourse. This conceptual framework is based on the assumption that the contextual findings of the literature may enhance understanding of the sustainability-wide choices that influence firms. It seeks to address the key sustainability factors/antecedents as established by Collins et al. (2007) . This framework is used to explore MNCs' sustainability antecedents for firms in China. Image 1 Highlights: Develops a conceptual framework for examining sustainability and cleaner production. Recognizes motivators for implementing sustainability practices in Multinational firms. Identifies differences in sustainability performances based on Multinational firm size. Provides recommendations on enhancing sustainability initiatives within host countries.